Efficacy of CT Guided Pulsed Radiofrequency Treatment for Trigeminal Postherpetic Neuralgia - Ding, Yuanyuan; Hong, Tao; Li, Hongxi; Yao, Peng; Zhao, Guangyi (Frontiers in Neuroscience, 2019)
Objectives: Trigeminal postherpetic neuralgia (TPHN) often presents with moderate to severe pain, hyperalgesia, and allodynia. Conventional analgesic treatments are poorly effective, which seriously affects the quality of life. This retrospective study aimed to evaluate the efficacy of pulsed radiofrequency (PRF) for the treatment of TPHN. Methods: A total of 90 TPHN patients were selected between January 2014 and December 2016 in the Department of Pain Management, Shengjing Hospital, China Medical University. Patients were randomly divided into 2 groups according to the order of enrollment (n=45 per group): group A, peripheral nerve (supraorbital nerve, infraorbital nerve and mental nerve) PRF; group B, gasserian ganglion PRF. Follow-up assessments of Visual Analogue Scale (VAS) pain assessment, SF-36 health status questionnaire, total efficiency rate, and drug dosage of anticonvulsants and opioid analgesics were performed at time points of 1 week, 1 month, 3 months, 6 months, and 1 year after surgery. Results: At each postsurgery time point, the VAS decreased, SF-36 (physical and mental components) increased, and drug dosage of anticonvulsants and opioids analgesics decreased in both treatment groups; values at each time point were significantly different from presurgery values (P<0.05). Compared with group A, VAS decreased, SF-36 increased, and dosage of anticonvulsants and opioids analgesics decreased significantly in group B (P<0.05). The total efficiency rates one year after surgery in group A and group B were 68.9% and 86.7%, respectively. The total efficiency rate of group B was statistically higher than that of group A (P<0.05). Conclusion: PRF relieved TPHN, and gasserian ganglion PRF was more effective than peripheral nerve PRF. The method was effective and improved the quality of life of the patients. PRF is recommended as a treatment for TPHN.